Proteomics of the acid-soluble fraction of whole and major gland saliva in burning mouth syndrome patients. (February 2019) - Cabras, Tiziana; Manconi, Barbara; Castagnola, Massimo; Sanna, Maria Teresa; Arba, Morena; Acharya, Shikha; Ekström, Jörgen; Carlén, Anette; Messana, Irene
Highlights: Top-down proteomics was applied to investigate salivary proteins in BMS patients. BMS patients showed cystatin SN levels in resting saliva higher than healthy controls. High SN levels could be a response to an ongoing oral inflammation. Abstract: Objective: In the present study the salivary proteome of burning mouth syndrome patients and healthy subjects was characterized by a top-down proteomic approach and compared to highlight possible qualitative and quantitative differences that may give suggestions about the causes of this pathology which are still unknown. Materials and methods: Resting and stimulated whole saliva, stimulated parotid and submandibular/sublingual saliva samples were collected from burning mouth syndrome patients (n = 16) and age- and gender-matched healthy subjects (n = 14). An equal volume of 0.2% trifluoroacetic acid was added to each sample immediately after collection and the supernatants were analysed by liquid chromatography coupled to electrospray-ionisation mass spectrometry. Proteins and peptides were quantified using a label-free approach measuring the extracted ion current peak areas of the main salivary proteins and peptides. Results: The quantitation of the main salivary proteins and peptides revealed a higher concentration of cystatin SN in resting saliva of burning mouth syndrome patients with respect to healthy controls and no other conspicuous changes. Conclusions: The reported data showed that the salivary protein profile was not affected, in composition and relative abundance, by the burning mouth syndrome, except for the cystatin SN, a protein up-regulated in several pathological conditions, that might be considered potentially indicative of the disease.